From Bill Goodwine's Wiki

Revision as of 12:46, 10 November 2012 by Goodwine (talk | contribs) (Created page with "The equation should be <math>\ddot x(t) = \sum_{n+2}^\infty n(n-1)a_n t^{n-2} = \sum_{n=0}^\infty (n+2)(n+1)a_{n+2}t^n </math> [[Engineering Differential Equations: Theory and ...")

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

The equation should be

${\ddot {x}}(t)=\sum _{n+2}^{\infty }n(n-1)a_{n}t^{n-2}=\sum _{n=0}^{\infty }(n+2)(n+1)a_{n+2}t^{n}$

- This page was last edited on 10 November 2012, at 12:46.
- Content is available under Attribution-Share Alike 3.0 Unported unless otherwise noted.
- Privacy policy
- About Bill Goodwine's Wiki
- Disclaimers